Learning how to teach: portrait of teaching skills of tadris mathematics students in microteaching courses - Syahid, Ibnu Amirus; Astuti, Wiwin; Wibowo, Ari (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2025)
Abstract. Teaching skills are one of the essential competencies that education students must possess as prospective teachers. However, in reality, many students still struggle to implement teaching skills effectively during microteaching courses. This study aims to analyze the teaching skills of Tadris Mathematics students in microteaching courses. The method employed in this research is descriptive quantitative. Data were obtained from the assessment sheets of the lecturers who taught the microteaching course. The sample comprised all Tadris Mathematics students at UIN Raden Mas Said Surakarta, semester 6, who enrolled in microteaching courses, totaling 82 students divided into six classes. The results indicated that there are four indicators of teaching skills in the very good category, eight indicators in the good category, ten indicators in the adequate category, and three indicators in the poor category. Students demonstrated excellent opening and closing skills and demonstrated positive verbal and nonverbal performance, such as clear language use and an attractive appearance. However, they still needed reinforcement in developing HOTS skills, implementing the TPACK approach and problem or project based learning, and developing HOTS based assessments. Thus, there remains a dominance of teaching skill indicators that fall within the adequate and poor categories, highlighting the need for further intervention and improvement. Each student's teaching skills improved from the first to the third practice. The variation in teaching skills among students decreased, demonstrating that students' teaching skills became more uniform and stable. Most of the students fall into the good and very good categories. The development of students' teaching skills is supported by four vital principles in microteaching learning, namely the principle of practice, the principle of reinforcement, the principle of evaluation, and the principle of precision supervision. This research is expected to provide an understanding of the role of microteaching in shaping the teaching skills of prospective teachers and a basis for developing more effective microteaching strategies.